Crisis, Liturgy and the Crusade in the Twelfth and Thirteenth Centuries - Maier, Christoph T. (The journal of ecclesiastical history, 1997)
The First Crusade has been described as a ‘church in procession’ and a ‘military monastery on the move’. The progress of the first crusading armies to the Holy Land was indeed accompanied by regular liturgical practices, acts of devotion and intercessory rites. Before each battle and during sieges the crusaders fasted, prayed, celebrated mass and confessed their sins. They went in processions and sang psalms. This wealth of liturgical practices reported by contemporary commentators provided the rhythm to the crusaders' pilgrimage to Jerusalem and marked the sacred character of their undertaking. At the same time, the liturgy was a rallying point for the crusaders' identity: it represented and reinforced the special relationship between the milites Christi and their God, and gave expression to the spirituality and the ethos of the holy warrior. The crusaders' earnest participation in the liturgy of pilgrimage and holy war no doubt contributed to the image, already observed by contemporaries, of the crusade as a vehicle of piety and a means of salvation parallel to the vocation of the monastic life, which was traditionally considered the highest form of religious devotion.